(untitled) (Iranian Journal of Kidney Diseases, 2014)
Hemorrhagic fever with renal syndrome (HFRS) is a serious human disease of zoonotic viral origin. A group of different viruses that belong to the family of hemorrhagic fever could represent with HFRS. The basic pathophysiologic feature is virus-induced leaky microcirculation. There is no effective antiviral treatment against them. Because of rapid environmental changes, global warming, and increased global traveling, different hemorrhagic fever syndromes could be found anywhere in the world and beyond their old endemic borders. This review is a brief overview of HFRS in Iran during the early and mid-twentieth century.